Pengaruh Arus Kas Operasi Terhadap Peningkatan Kemampulabaan dan Pertumbuhan Perusahaan STUDI KASUS PADA PT. HOLCIM INDONESIA, TBK. - Munawar, Aang; Marpaung, Bintang Sahala (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Operational cash flow is cash from operational activities of a company. By operational cash flow, the company can decide the fund available for the operational activities. The operational cash flow will be paid attention by the company management because it’s beneficial for decision making. Operational cash flow which increases can be expected to increase profitability due to the operational cash flow of the company will be able to decide how to utilize the fund available for the operational activities, but it must be accompanied by efficiency in the matter of operational expenses and the main cost of selling. By the increase of operational cash flow, it can be expected to raise the companies growth in selling due to the increase of operational cash flow of the company, it can rise production capacity which will be able to rise selling. In this study the author used a formula for operational cash flow (X) is operational cash flow on selling, a formula for profitability is profit margin, while for the company’s growth is salest – salest-1 – to salest-2. Moreover, the author utilized common size analysis, that is horizontal common size and vertical common size. Regression test result on PT. Holcim Indonesia, Tbk shows significance result of 0% from operational cash flow toward profit, which indicates that operastional cash flow has an effect with significance level as high as 10%. From regression test result of operational cash flow on the company’s growth, it’s obtained significance result of 9,2%, which indicates that there is an effect with significance level as high as 10%. Keywords : Operational cash flow; profitability; growth